2014
DOI: 10.3109/09637486.2013.879288
|View full text |Cite
|
Sign up to set email alerts
|

Increased muscular triglyceride content and hyperglycemia in Goto-Kakizaki rat are decreased by egg white hydrolysate

Abstract: We investigated the fat metabolic characteristics in non-obese and diabetic Goto-Kakizaki (GK) rat and the effects of dietary egg white hydrolysate (EWH) on glucose and fat metabolism. Wistar (W) and GK (G) rats were placed into dietary casein (WC and GC) or EWH (WE and GE) group, and fed their respective diet for six weeks. Triglyceride (TG) content and stearoyl-CoA desaturase (SCD) indices in the soleus muscle were higher in the GC group than WC group in parallel with worsening serum glucose metabolic parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 50 publications
4
26
0
Order By: Relevance
“…However, few reports have investigated the nutritional effects of EWH. In our previous study, dietary EWH decreased triacylglycerol (TAG) accumulation in muscles and liver in spontaneous diabetic Goto-Kakizaki rats (4). We also showed suppressive effects of EW and EWH on fat accumulation not only in the liver and muscles but also in intra-abdominal adipose tissues and carcasses of normal rats fed a high-fat and high-sucrose diet (HFSD) ad libitum (5).…”
mentioning
confidence: 66%
“…However, few reports have investigated the nutritional effects of EWH. In our previous study, dietary EWH decreased triacylglycerol (TAG) accumulation in muscles and liver in spontaneous diabetic Goto-Kakizaki rats (4). We also showed suppressive effects of EW and EWH on fat accumulation not only in the liver and muscles but also in intra-abdominal adipose tissues and carcasses of normal rats fed a high-fat and high-sucrose diet (HFSD) ad libitum (5).…”
mentioning
confidence: 66%
“…We have also reported that EWH improves fasting serum glucose and insulin levels in diabetic Goto-Kakizaki (GK) rats (1) and Wistar rats (2). These findings suggest that in addition to improving fat metabolism, EWH can prevent the onset of glucose intolerance and T2DM.…”
mentioning
confidence: 67%
“…Fecal excretion of TG and CHO was numerically higher in the NE and NEH groups than that in the NH groups although the fecal weights and fecal total lipids content were equal (Table 2). From the results of lipids analyses, EW clearly suppressed CHO accumulation, which is supposed to be caused by lower lipid absorption and fat synthesis (1)(2)(3)26). EWH slightly suppressed the CHO accumulation, but the effect was weakened compared to EW.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations